The Effect Of Basic Life Support Training On Basic Life Support Knowledge In ‘Aisyiyah Cadre - Dian Yuliartha Lestari; Abi Noerwahjono; Cindy Savira (Universitas Muhammadiyah Malang, 2020)
Background: Basic life support or BLS is an early emergency intervention cases which possibly happens anywhere. BLS is important to be given accurately and immediately not only by healthcare professionals but also by lay people in order to give early intervention towards emergency cases until medical teams arrives. ‘Aisyiyah cadre, as part of the society, are expected to be able to give early intervention that is BLS correctly.Objective: To assess the impact of basic life support training on the knowledge of ‘Aisyiyah cadre towards basic life support.Method: This study is a analytical observational study with cross-sectional approach. The sample of this study is 38 participants which are ‘Aisyiyah cadre from Malang city. Participants included on this study are those who do not have any medical background. Data analysis were using wilcoxon test.Result and discussion: 13 participants were having knowledge improvement, 24 participants did not have any improvements, and one of the participants were having degradation of knowledge level after the BLS training were given. According to wilcoxon test, the p-value was 0,001 which means that the BLS training given have positive impact on the improvement of ‘Aisyiyah cadre’s knowledge towards BLS.Conclusion: There is a significant impact between BLS training on the knowledge of ‘Aisyiyah cadre towards BLS which indicates that the BLS training given have postivive impact on the improvement of ‘Aisyiyah cadre’s knowledge towards BLS.